The Role of Advanced Academic Literacy Development in Enhancing Academic Writing and Publishing: A Narrative Inquiry of Indonesian Doctoral Students - Wahyuningsih, Sri; Widiati, Utami; Basthomi, Yazid (FKIP Universitas Lampung, 2025)
The Role of Advanced Academic Literacy Development in Enhancing Academic Writing and Publishing: A Narrative Inquiry of Indonesian Doctoral Students. Objectives: Academic writing and publishing are crucial elements of doctoral education, yet many Indonesian doctoral students face significant challenges in developing the advanced academic literacy necessary for scholarly publishing. Methods: Employing a narrative inquiry approach, this study explores the lived experiences of five doctoral students from five universities in Indonesia. Data were gathered through semi-structured interviews. Findings: Findings reveal that structured academic literacy programs, mentorship, and exposure to scholarly discourse play a crucial role in improving students’ writing and publishing capabilities. However, persistent challenges, including linguistic barriers, institutional constraints, and the pressures of the ‘publish or perish’ culture, hinder their progress. Conclusion: The study underscores the need for higher education institutions to provide comprehensive academic literacy training, sustained mentorship, and collaborative research opportunities to support doctoral students in achieving academic publishing success. These insights contribute to a broader understanding of the interplay between academic literacy and research productivity, with implications for doctoral education policies and scholarly writing development programs. Keywords: academic literacy, academic writing, doctoral education, Indonesian higher education, scholarly publishing.